The effect of processing conditions on the characteristics of electrically conductive thermoplastic composites - Carneiro, O. S. (2012)
Carbon black (CB) thermoplastic composites are extensively used in antistatic, electrostatic dissipative, and semiconductive applications, where a relatively low electrical conductivity and low material costs are required. Achieving the adequate mixing levels during compounding is a major practical requirement. The present work studies the preparation by twin-screw extrusion of conductive composites containing ca. 20% weight-in-weight (w/w) CB, by investigating the effects of the processing conditions and of small variations in the filler’s feeding rate on the evolution of the relevant processing parameters and rheological response along the extruder axis and of the electrical properties.